Spatial Distribution and Environmental Risk of Arsenic and Antimony in Soil Around an Antimony Smelter of Qinglong County - He, Yingping; Han, Zhiwei; Wu, Fuzhong; Xiong, Jia; Gu, Shangyi; Wu, Pan (Bulletin of environmental contamination and toxicology, 2021)
The purpose of this study was to investigate the distribution of arsenic (As) and antimony (Sb) in soils around an antimony smelter at Qinglong together with the soil pollution levels and potential ecological risk. The results show that (1) total concentrations of As (23 ~ 539 mg/kg) and Sb (19.7 ~ 5681 mg kg −1 ) were higher than the Guizhou province-level background values (As, 20; Sb, 2.24), especially Sb. Their dominant geochemical speciation was the residual fraction which accounted for > 90% of the total concentrations. (2) The distribution of As and Sb in soils influenced mainly by land-use type, altitude, predominant wind direction, and distance from the pollution source. (3) The geo-accumulation index shows that the soil was highly contaminated with Sb and moderately with As. The potential ecological risk index shows that As posed a moderate risk and Sb a high risk. The general ecological risk was classified as high risk. However, the risk index coding method shows low environmental risk from As and Sb.